2020
DOI: 10.3389/fmicb.2019.03044
|View full text |Cite
|
Sign up to set email alerts
|

Functional Signatures of the Epiphytic Prokaryotic Microbiome of Agaves and Cacti

Abstract: Flores-Núñez et al. Epiphytic Metagenomes of Agaves and Cacti mechanisms by which epiphytic microbial communities survive and colonize plants of arid and semiarid ecosystems. This study establishes a guideline for testing the relevance of the identified functional traits on the microbial community and the plant fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…Furthermore, QS helps in selecting and shaping the bacterial partners with specific PGPR and biocontrol functions thereby benefiting plants to achieve optimum fitness (Hartmann et al, 2014;Altaf et al, 2017;Zaytseva et al, 2019). Such PGPR can be found enriched in the rhizospheres of desert plants such as Agave and cacti (Flores-Núñez et al, 2020).…”
Section: Application Of Desert Pgpr For Sustainable Agriculturementioning
confidence: 99%
“…Furthermore, QS helps in selecting and shaping the bacterial partners with specific PGPR and biocontrol functions thereby benefiting plants to achieve optimum fitness (Hartmann et al, 2014;Altaf et al, 2017;Zaytseva et al, 2019). Such PGPR can be found enriched in the rhizospheres of desert plants such as Agave and cacti (Flores-Núñez et al, 2020).…”
Section: Application Of Desert Pgpr For Sustainable Agriculturementioning
confidence: 99%
“…The differences in microbial community structure between wild and cultivated plants have been reported for different species of Agave ( Coleman-Derr et al, 2016 ; Fonseca-García et al, 2018 ) suggesting that cultivation of A. tequilana negatively influences its microbial diversity. A recent report ( Flores-Nuñez et al, 2020 ) approached by shotgun metagenome analysis, pointed again in the same direction; the rhizospheric bacterial community of A. tequilana was less diverse than that of wild A. salmiana , and other wild cacti. Although their cultivated and native non-rhizospheric soil samples showed similar diversities.…”
Section: Discussionmentioning
confidence: 71%
“…Specifically, the relative abundance of Pseudoalteromonas in groups A and D decreased more than five-fold after QSI-treatment, compared with that of the control group (group C). Numerous reports have shown that biofilm formation is closely associated with Pseudoalteromonas (a typical bacterium that relies heavily on QS), which could regulate microbial population and help other bacteria colonize [30][31][32]. Like Pseudoalteromonas, Halomonas is also a QS producer that is sensitive to QSI.…”
Section: Discussionmentioning
confidence: 99%